Non-isothermal analysis of calendering using couple stress fluid. (October 2018) - Ali, Nasir; Javed, Muhammad Asif; Atif, Hafiz Muhammad
The non-isothermal flow inside a calender is modeled and analyzed for a couple stress fluid. The governing flow equations are developed using conservation laws of mass, momentum and energy. An order of magnitude analysis is performed and leading terms in momentum and energy equations are retained. The reduced momentum equation is solved to obtain the exact expression for velocity and pressure gradient. The reduced energy equation is solved numerically using a hybrid numerical method. The significant effects of the involved parameters on the pressure, pressure gradient velocity profile, roll-separating force, power input, exiting sheet thickness and temperature are examined through various plots. The pressure inside the calender significantly increases with increased couple stress effects. For larger couple stress parameters, the power function and roll-separating function show steady state behavior. The two maxima are distinctly observed in temperature distribution near the roll surfaces for small couple stress effects( γ → ∞ ) . In contrast, the temperature achieves maximum at center for strong couple stress effects( γ → 0 ) .